Inappropriate Shocks in Patients With Fidelis® Lead Fractures: Impact of Remote Monitoring and the Lead Integrity Algorithm. - BLANCK, ZALMEN; AXTELL, KATHI; BRODHAGEN, KATHY; O'HEARN, LAURA; ALBELO, TAMMY; CERETTO, CHERYL; DHALA, ANWER; SRA, JASBIR; AKHTAR, MASOOD (Journal of Cardiovascular Electrophysiology, 2011)
Prevention of Shocks With Fidelis Lead Fractures. Introduction: The role of remote monitoring combined with lead integrity algorithm (LIA) in patients with Fidelis (Medtronic Inc., Minneapolis, MN, USA) lead fractures is not well defined. Methods: We retrospectively identified patients with Fidelis lead fractures at our institution, documenting all pertinent data (remote monitoring use, clinical presentation, lead fracture diagnosis criteria). Patients were classified into subgroups based on the type of home monitoring and whether LIA was uploaded before lead fracture. Subgroups were compared based on delivery of inappropriate shocks (IS). Results: A total of 131 patients (mean age 62 ± 16 years, 70% male, 69% primary prevention implants) were followed until lead fracture (average 32 ± 12 months). IS were delivered in 21% of patients (n = 11/52) with LIA versus 52% (n = 41/79) without LIA, P < 0.001. LIA significantly decreased the number of IS (2.1 ± 1.0 IS vs 7.9 ± 12 IS, P < 0.001) and significantly increased the number of patients diagnosed through audible alert (P < 0.001). Wireless monitoring significantly decreased the time interval to reprogram defibrillators OFF (mean 1.5 ± 1 days vs 15.6 ± 18 days with nonwireless CareLink [Medtronic Inc.] and 12.4 ± 20 days without CareLink, P < 0.001); 14% of patients with LIA and wireless monitoring combined received IS. Without LIA, 63% of patients with wireless monitoring received IS. Conclusion: This study confirms that LIA significantly decreases IS therapy in patients with Fidelis lead fractures. Wireless technology enhances LIA benefits by significantly shortening time to reprogram defibrillators. However, despite the 'best scenario' of combining LIA and wireless monitoring, 14% of patients with lead fractures still get IS. Further refinements of detection algorithms are required to eliminate this significant clinical problem. (J Cardiovasc Electrophysiol, Vol. 22, pp. 1107-1114, October 2011)